(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The worldwide 4 per 1000 project seeks to assist governments and non-governmental organizations in their efforts to improve soil carbon (C) stock management. These stocks are depending on soil C emissions and inputs. They are the result of interconnected fine-scale mechanisms that stability or dissolve C carried by biological materials. The Carbo SMS cooperation has drawn together French academics specializing in these phenomena and their influence on C stores in the context of regional and global change since 2016. This article summarizes the first seminar of this partnership. In the first part, we discuss recent advances in our understanding of soil C anchoring methods, which comprise abiotic stresses processes that occur concurrently and interact. Plants (the principal source of carbon via debris but also root systems), microorganisms (fungi and bacteria), and ’environment engineers’ all have an impact on soil organic carbon stocks (earthworms, termites, ants). Abiotic mechanisms that are related to soil crystal properties, opacity, and material fraction on the other hand, affect these stocks. We demonstrate how agricultural methods influence soil C stocks in the second half. Land use and management methods affect both biotic and abiotic processes. We address several proxies and models that describe particular processes and their activity. In diverse soil and environmental situations, as well as how to incorporate them into large-scale models to improve soil C stock change estimates. Furthermore, this literature review highlights future scientific investigations targeted at preserving or even increasing C stocks, with a focus on procedures, farming practices’ effects on them, and C inventory forecasting models.